2020
DOI: 10.1080/02757540.2020.1817403
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in Gobi soils of the northeastern Qinghai-Tibet Plateau

Abstract: This study investigated the pollution, potential ecological risks, and possible sources of trace elements in Gobi soils of the northeastern Qinghai-Tibet Plateau. Contents of Hg in soils were below the detection limit. The average contents of the remaining trace elements in soils ranged from 0.21 (Cd) to 2360.82 (As) mg/kg. Multiple methods were used to evaluate the soil pollution of the study area. Pb posed the most serious pollution based on geoaccumulation index evaluation. As showed the strongest enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…It is worth mentioning that the correlations between As, Ba, U, and other elements were all relatively weak. There was no obvious correlation between As and other elements, which is a similar finding to other research [ 10 , 48 ]. The predominant reason for this finding is that As mainly derives from anthropogenic sources, such as industrial activities [ 35 , 49 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It is worth mentioning that the correlations between As, Ba, U, and other elements were all relatively weak. There was no obvious correlation between As and other elements, which is a similar finding to other research [ 10 , 48 ]. The predominant reason for this finding is that As mainly derives from anthropogenic sources, such as industrial activities [ 35 , 49 ].…”
Section: Resultssupporting
confidence: 90%
“…Fuel combustion, oil combustion, and brake pad wear will cause enrichment of Cd, Pb, Zn, Cu, and other elements [ 52 ]. For example, the emission of Zn in automobile lubricants, the decomposition of trace element components in automobile tires, Cd is mostly derived from engine oils, abrasion of brake linings, and tearing of tires, and the emission of Cd and Cu will all cause enrichment of relevant trace elements [ 48 , 53 ]. Pb mainly comes from the release of leaded gasoline and kerosene [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the non-carcinogenic risks for dermal contact and ingestion were lower in residential and recreational adults than in children. This suggested that adults were less susceptible than children when subjected to HMs in water, which was in line with the conclusions of earlier investigations (Xiao et al, 2019;Li et al, 2020b;Aravinthasamy et al, 2021;Karunanidhi et al, 2021c;Karunanidhi et al, 2021d;Li D. et al, 2022). Saline, however, was unfit for drinking, so the health risk from ingestion was not calculated.…”
Section: Non-carcinogenic and Carcinogenic Risks In Surface Watersupporting
confidence: 80%
“…Physicochemical, microbiological, and trace element parameters of water are the most commonly used indicators to determine the health of water bodies. On the other hand, heavy metals in water bodies are among the most dangerous pollutants due to their persistence, carcinogenicity and environmental toxicity [13][14][15][16][17]. Many regions of the planet face severe water pollution, especially heavy metals [12,[18][19].…”
Section: Introductionmentioning
confidence: 99%